2009
DOI: 10.1093/nass/nrp063
|View full text |Cite
|
Sign up to set email alerts
|

Unnatural imidazopyridopyrimidine:naphthyridine base pairs: selective incorporation and extension reaction by DNA polymerases

Abstract: We describe herein the results of (i) enzymatic recognition for imidazopyridopyrimidine (Im):naphthyridine (Na) base pairs and (ii) further primer extension reactions after the Im:Na base pairs by DNA polymerases. Among the base pairs examined, ImN(O):NaO(N) base pair was rather selectively recognized by Klenow fragment exo(-) [F(exo(-))]as complementary base. However, this DNA polymerase did not catalyze primer extension reactions after the ImN(O):NaO(N) base pair. Therefore, we carried out a screening of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The tip of the thumb domain makes contacts with the primer strand, whereas the architectures of the contacting loops differ greatly: the loop in Therminator structure hoves above the minor groove without extending deeply into it, while the corresponding loop in Taq extends over the phosphate backbone toward the major groove . Furthermore, crystallographic studies have shown a higher-ordered interaction in the minor groove of the double helix DNA with family A polymerases compared to family B polymerases . Because the contacts of all sugars and nucleobases are through the minor groove, l -T nucleotide might clash with the tip of the domain when processed by Taq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tip of the thumb domain makes contacts with the primer strand, whereas the architectures of the contacting loops differ greatly: the loop in Therminator structure hoves above the minor groove without extending deeply into it, while the corresponding loop in Taq extends over the phosphate backbone toward the major groove . Furthermore, crystallographic studies have shown a higher-ordered interaction in the minor groove of the double helix DNA with family A polymerases compared to family B polymerases . Because the contacts of all sugars and nucleobases are through the minor groove, l -T nucleotide might clash with the tip of the domain when processed by Taq.…”
Section: Resultsmentioning
confidence: 99%
“…39 Furthermore, crystallographic studies have shown a higher-ordered interaction in the minor groove of the double helix DNA with family A polymerases compared to family B polymerases. 50 Because the contacts of all sugars and nucleobases are through the minor groove, L-T nucleotide might clash with the tip of the domain when processed by Taq. Thus, Taq shows no tolerance for L-T in the template, whereas better performance of B-family polymerases in processing L-T may be the result of a sterically less-hindered minor groove.…”
Section: Bioconjugate Chemistrymentioning
confidence: 99%